THE EFFECT OF PERCEIVED BENEFIT AND PERCEIVED BARRIER ON ACTIVITY OF DAILY LIVING IN NON-HEMORRHAGIC STROKE POST PATIENTS (Proceedings of the International Conference of Community Health and Medical Sciences, 2024)
Stroke is one of the leading causes of death and disability worldwide. Stroke is classified into two, namely non-hemorrhagic stroke and hemorrhagic stroke. The incidence of non-hemorrhagic stroke is higher than hemorrhagic stroke. Non-hemorrhagic post-stroke events can lead to functional disability and decreased quality of life which can affect the physical, psychological, and social so as to reduce the quality of life of non-hemorrhagic post-stroke patients. This can be overcome if the patient has perceived benefits and perceived barriers which are aspects of the health belief model. The purpose of this study was to determine the effect of perceived benefits and perceived barriers on the activity of daily living in post-stroke non-hemorrhagic patients. This research is quantitative research with a cross-sectional study design. The samples were post-stroke non-hemorrhagic patients undergoing outpatient treatment at the geriatric clinic of KRMT Wongsonegoro Hospital from October-November 2022 who met inclusion and exclusion criteria as many as 80 respondents. The method used to measure the perceived benefit and perceived barrier variables is to use a questionnaire in the form of statements that are measured using an ordinal scale. Meanwhile, to measure the activity of daily living the researchers used the barthel index. Then the researcher tested the hypothesis using Spearman's rank correlation so that the results of the analysis of the perceived benefit variable were obtained (p=0.044) with a correlation coefficient of -0.225 and perceived barrier variables (p=0.865) with a correlation coefficient of -0.019. There was a significant effect between perceived benefit on the activity of daily living in non-hemorrhagic post-stroke patients and there was no effect between perceived barrier and activity of daily living in non-hemorrhagic post-stroke patients.
Keywords: activity of daily living; non-hemorrhagic stroke post patients; perceived benefit